Retrieval of Trichostrongylus colubriformis infective larvae from grass contaminated in winter and in spring - Rocha, Raquel Abdallah da; Bricarello, Patrizia Ana; Rocha, Gilberto Pedroso da [UNESP]; Talamini do Amarante, Alessandro Francisco [UNESP] (Brazilian Coll Veterinary Parasitology, 2014)
The survival of infective larvae (L3) of Trichostrongylus colubriformis was evaluated on Brachiaria, Coast-cross and Aruana forage grasses. Feces of sheep parasitized exclusively by T. colubriformis were deposited in winter and spring on experimental plots whose grasses were cut at two heights: 5 cm and 30 cm. One, two, four, eight, 12 and 16 weeks after depositing the feces, fecal and forage samples were collected for the retrieval and quantification of L3. Retrieval of L3 from feces and forage was negligible in winter due to the dry weather, although a few larvae were retrieved in the last larval collections. However, L3 retrieval from fecal samples was greater in spring, especially two weeks after feces were deposited on 30 cm high grasses. At this time, the L3 retrieval rate from the three forage grasses differed significantly (P < 0.05), with Aruana grass showing the highest average L3 retrieval rate, followed by Coast-cross and Brachiaria. In conclusion, the winter drought proved very unfavorable for the presence of L3 in the environment, and the microclimate of Aruana pastureland was generally the most favorable for the retrieval of infective larvae.

A sobrevivência de larvas infectantes (L3) de Trichostrongylus colubriformis foi avaliada em pastagem de Braquiária, Coast-cross e Aruana. Fezes de ovinos parasitados exclusivamente por T. colubriformis foram depositadas no inverno e na primavera em parcelas experimentais com duas alturas de corte da forragem, 5 cm e 30 cm. Uma, duas, quatro, oito, 12 e 16 semanas após o depósito, amostras de fezes e de forragem foram coletadas para a recuperação e quantificação de L3. Devido à seca no inverno, a recuperação de L3 das fezes e da forragem foi ínfima, embora tenha havido recuperação de algumas larvas nas últimas coletas. Por outro lado, na primavera houve maior recuperação de L3 das amostras, especialmente duas semanas após a deposição das fezes em meio às pastagens com 30 cm de altura. Nesse momento, houve diferença significativa (P<0,05) entre as três forrageiras, com maior média de L3 no capim Aruana, seguido de Coast-cross e Braquiária. Em conclusão, a seca registrada no período de inverno se mostrou bastante desfavorável à presença de L3 no ambiente e, de forma geral, o microclima da pastagem de Aruana foi o que mais favoreceu a recuperação de larvas infectantes.
Keywords: Sheep; Nematodes; Epidemiology; Brachiaria decumbens; Panicum maximum; Cynodon dactylon